Pengaruh Return on Equity, Earning Per Share dan Debt to Equity Ratio terhadap Harga Saham Syariah - Dewi Kurnia; Dhea Prika Aprilliana; Nana Diana (Akuntansi : Jurnal Akuntansi Integratif, 2020)
This study aims to examine the effect of ROE, EPS, and DER on Shariah stock prices and to find out and analyze which variables provide the most dominant influence on sharia stock prices in automotive subsector manufacturing companies listed on ISSI. The research sample was taken using a quantitative method with a descriptive approach. The analysis technique is multiple regression analysis. The sample used was 8 companies during the 2015-2018 period so that the total data processed was 32 data. Data collection is done by means of documentation that is taking data from the internet. The results of the analysis show that ROE partially has a positive and significant effect on Sharia Share Prices. Whereas EPS, and DER have a negative effect on Sharia stock prices